Werner Marx and Martin Heidegger: What “Measure” for a Post-metaphysical Ethics? - Swazo, Norman K. (Conatus - Journal of Philosophy, 2024)
German philosopher Martin Heidegger’s later thought is significant because of his attention to the meaning of “truth” (alētheia) and its connection to Protagoras’s thesis of anthrōpon metron (“of all things man is the measure…”), which Heidegger elevates to the “highest principle” of philosophy. Philosopher Werner Marx concurs with Heidegger that our time faces the “age of technology” as the completion of the Western tradition of metaphysics. With the “end of philosophy” in this sense, we stand to inaugurate “a new beginning” in thinking without reliance on the principles and standards that have their provenance in the tradition from ancient Greek philosophy onward to late European modernity. For Marx, this elicits the possibility of a non-metaphysical ethics, hence the question of “measure” that he engages in connection with Heidegger’s later thinking. However, it is problematic that Marx engages Schelling’s reflections on the essence of human freedom to articulate a possibility of measure. Here Marx’s reflections are engaged by considering his motivation and the thought of Schelling, Nietzsche, Heidegger, as well as the historical context of the twentieth century, all of which constrain Marx’s normative objective. Heidegger’s engagement of Schelling and Kant to elucidate the problem of human freedom raises questions whether Marx’s proposal for a measure “on this earth” can achieve the goal of a foundation for a post-metaphysical ethics.